2011
DOI: 10.1149/1.3501970
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Oxidant on the Chemical and Field-Effect Passivation of Si by ALD Al[sub 2]O[sub 3]

Abstract: Differences in Si surface passivation by aluminum oxide ͑Al 2 O 3 ͒ films synthesized using H 2 O and O 3-based thermal atomic layer deposition ͑ALD͒ and plasma ALD have been revealed. A low interface defect density of D it = ϳ 10 11 eV −1 cm −2 was obtained after annealing, independent of the oxidant. This low D it was found to be vital for the passivation performance. Field-effect passivation was less prominent for H 2 O-based ALD Al 2 O 3 before and after annealing, whereas for as-deposited ALD films with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
138
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 20 publications
12
138
0
Order By: Relevance
“…Thus it is concluded that a large part of the improvement in passivation occurring after thermal treatment of ALD deposited alumina originates from increasing the concentration of negative charge in the films. This is in agreement with previous ALD Al2O3 work performed in flat silicon [36]. For pyramidal surfaces, however, lower passivation quality is observed with respect to hybrid and SiNW surfaces.…”
Section: Interface Recombinationsupporting
confidence: 92%
“…Thus it is concluded that a large part of the improvement in passivation occurring after thermal treatment of ALD deposited alumina originates from increasing the concentration of negative charge in the films. This is in agreement with previous ALD Al2O3 work performed in flat silicon [36]. For pyramidal surfaces, however, lower passivation quality is observed with respect to hybrid and SiNW surfaces.…”
Section: Interface Recombinationsupporting
confidence: 92%
“…However, on p-type Si, the SiO x / SiN x stack was clearly superior to the single layer SiN x . The level of passivation induced by atomic layer deposited ͑ALD͒ Al 2 O 3 , containing Ͼ5 ϫ 10 12 cm −2 negative charges, 16 was higher, but not substantially so, than that for the stacks, as shown in Fig. 1.…”
mentioning
confidence: 78%
“…Furthermore, the thermal stability ͑up to 850°C͒ of the stack was found to be very high, which can be ascribed to effective hydrogenation of the Si/ SiO x interface under influence of the SiN x layer. The results presented are especially timely because various lowtemperature passivation schemes, such as aluminum oxide ͑Al 2 O 3 ͒, [14][15][16] are currently under evaluation as replacements for the standard aluminum back surface field in solar cells with thinner Si wafers.…”
mentioning
confidence: 99%
“…It has been reported by Dingemans et al [13] and Terlinden et al [28] that those stacks exhibit excellent chemical passivation levels (e.g., D it values o 10 11 eV À 1 cm À 2 at mid gap [32]), while their Q f can effectively be tuned from strongly negative up to zero or even positive values by carefully tuning the ALD SiO 2 thickness. It is hypothesized that for these stacks the SiO 2 interlayer acts as a (trap-assisted) electron tunnel barrier, preventing charge-injection from the c-Si base into the electron trap sites in the Al 2 O 3 [13,28].…”
Section: Introductionmentioning
confidence: 99%